DUAL SPECIATION OF NITROGEN IN SILICATE MELTS AT HIGH PRESSURE AND TEMPERATURE: AN EXPERIMENTAL STUDY - Roskosz M.; Mysen B.O.; Cody G.D. (My University, 2006)
Solubility and speciation of nitrogen in silicate melts have been investigated between 1400 and 1700 °C and at pressures ranging from 10 to 30 kbar for six different binary alkali and alkaline-earth silicate liquids and a Ca-Mg-alumino silicate. Experiments were performed in a piston-cylinder apparatus. The nitrogen source is silver azide, which breaks down to Ag and molecular N2 below 300 °C. At high pressure and temperature, the nitrogen content may be as high as 0.7 wt% depending on the melt composition, pressure, and temperature. It increases with T, P and the polymerization state of the liquid. Characterization by Raman spectroscopy and 15N solid state MAS NMR indicates that nitrogen is not only physically dissolved as N2 within the melt structure like noble gases, but a fraction of nitrogen interacts strongly with the silicate network. The most likely nitrogen-bearing species that can account for Raman and NMR results is nitrosyl group. Solubility data follow an apparent Henry's law behavior and are in good agreement with previous studies when the nitrosyl content is low. On the other hand, a significant departure from a Henry's law behavior is observed for highly depolymerized melts, which contain more nitrosyl than polymerized melts. Possible solubility mechanisms are also discussed. Finally, a multi-variant empirical relation is given to predict the relative content of nitrosyl and molecular nitrogen as a function of P, T, and melt composition and structure. This complex speciation of nitrogen in melts under high pressure may have significant implication concerning crystal-melt partitioning of nitrogen as well as for potential elemental and isotopic fractionation of nitrogen in the deep Earth. © 2006 Elsevier Inc. All rights reserved.